PENERAPAN MODEL PEMBELAJARAN TEMATIK DALAM PENANAMAN NILAI KARAKTER BERBASIS NILAI BUDAYA MINANGKABAU KABUPATEN TANAH DATAR - Melisa Melisa (Horizon, 2021)
This study describes application of the thematic learning model in the cultivation of character values based on Minangkabau (case study of SDN 01 Batipuh Baruah Batipuh sub-district, SDN 21 rice field in the middle of Pariangan sub-district, and SDN 01 sub-distict Limo Kaum) flat land district. This research is motivated by. Application thematic learning models in the cultivation of character values based Minangkabau cultural values. This study used a descriptive qualitative appoarch with the research informants being the principal, first grade theacers first grade students. Technical analysis consist of data collection, data reduction, data presentation and drawing conclusions. The result of this study indicate that the learning planning stage of all teacers has done the planning before implementing the thematic learning model at school in the form of an educational calender, syllabus, annual program, semester program, and learning implementation plan (RPP). The application of thematic learning has been carried out well, the way in which the delivery of the teacher varies makes the impression of learning to be fun in the application of thematic learning teacher associates the learning material according to the conditions and circumstances around the conditions and circumstances around the students. The obstacles are complicated and complicatd assessments, lack of learning media such as infocus.